ASYNCHRONOUS LASER TRANSPONDERS FOR PRECISE INTERPLANETARY RANGING AND TIME TRANSFER - Degnan J.J. (My University, 2002)
Satellite laser ranging (SLR) and lunar laser ranging (LLR) systems are single-ended instruments, i.e. they measure the roundtrip transit time of a laser pulse to a passive optical reflector. Since such single-ended systems are incapable of ranging beyond the Moon to the planets, we consider the feasibility of a two-way asynchronous (i.e. independently firing) interplanetary laser transponder pair, capable of decimeter ranging and subnanosecond time transfer from Earth to a spacecraft anywhere within the inner Solar System. After introducing the transponder link equation and the concept of ''balanced'' transponders, we describe how range and time can be transferred between terminals, and preview the potential advantages of photon counting asynchronous transponders for interplanetary applications. We then develop mathematical models for the various sources of noise in an interplanetary transponder link including planetary albedo, solar or lunar illumination of the local atmosphere, and laser backscatter off the local atmosphere. After introducing the key engineering components of an interplanetary laser transponder, we develop an operational scenario for the acquisition and tracking of the opposite terminal. We then use the theoretical models of the previous sections to perform an Earth-Mars link analysis over a full synodic period of 780 days under the simplifying assumption of coaxial, coplanar, circular orbits. We demonstrate that, using slightly modified versions of existing space and ground based laser systems, an Earth-Mars transponder link is not only feasible but quite robust. We also demonstrate through analysis the potential advantages of compact, low output power (<300 mW), photon-counting transponders, which utilize NASA's developmental SLR2000 satellite laser ranging system as the Earth terminal and offer some concluding remarks regarding future applications.